Kierunki rozwoju systemów controllingowych i rachunkowości zarządczej banków - Lisowski, Mariusz (Trends of controllership in banks, 2006)
This article presents the basic elements of the banking controllership. At the beginning the factors in the financial markets are characterized. This article explains selected stages and actions of management in banks. It also contains information about instruments of banking controllership which are used in commercial banks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 238-243